The primate nervous system. - Bloom, Floyd E.; Bjorklund, Anders, 1945- (Handbook of chemical neuroanatomy, 1999)
This volume is the third and final part of the planned coverage of the neurochemical circuitry of the primate central nervous system. The five chapters included in this volume complement and integrate magnificently with the two prior volumes. Included in the volume are the following: a two-fold exposition on the human forebrain, comprised of a comprehensive overview of the entire human forebrain, and a specific focus on the basal forebrain (a region critical for a wide range of human problems ranging from substance abuse to Alzheimer's disease), a critical synthesis of the primate basal ganglia (a region under intense scrutiny for the organization of motor programs, and for their dysfunctions in Parkinson's disease, Huntington's disease and other malfunctions), the chemical and anatomic details of the primate hippocampal formation in extenso, and lastly, a review of the rapidly growing literature on the mesocortical projection of dopaminergic circuits onto the primate frontal cortex (a system highly linked to higher order mental abstractions, as well as the dysfunctions of schizophrenia). Scholars will recognize that the laying out of these status reports on our still vastly incomplete examination of the primate brains is an opportunity for progress.